The effect of metallic catalysts on the synthesis of GaN micro-crystals - Roh, CH; Park, YJ; Kim, EK; Shim, KB (ELSEVIER SCIENCE BV, 2002)
GaN micro-crystals have been synthesized by the direct reaction of NH3 with Ga-melt. The dark-gray colored GaN micro-crystals were obtained through the synthesis process at 1050degreesC for 311 in atmospheric NH3 ambient gas. In particular, the characteristics of the GaN micro-crystals obtained from a catalytic reaction with metallic Ni and Ti powders of 0.1 mol% were investigated using XRD, PL and SEM. It was found that the addition of Ni powder in the Ga-melt resulted in the decrease of the product yield but the increase of the PL peak intensity, and the controlled reduction of the crystallite size. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: VAPOR-PHASE EPITAXY; GROWTH; PROSPECTS; MELT